Proactive planning of project team members' competences - Eryk Szwarc; Jarosław Wikarek (Foundations of Management, 2020)
Among the many factors that cause project delays or cancellations are disruptions, that is, unforeseen events occurring during the implementation of a project, which postpone or interrupt the performance of project activities. Examples of disruptions include employee absenteeism, addition of new activities, and others. One way to deal with this type of events is to predict potential disruptions and prepare redundant resources to be used should a disruption occur (proactive approach). The focus of the present paper are human resources, in particular redundant project team competence frameworks, which allow to continue work on a project in the event of a disruption. Previous studies on planning competence frameworks regard insensitivity (robustness) to one type of disruption, caused by employee absenteeism (an absence of one, two, or three employees). The goal of this article is to present a proactive procedure that allows to seek competence frameworks robust to two types of disruptions: absence of one employee and addition of new activities not included in the project plan. Examples are provided to illustrate how the proposed approach can be used in practice.
Keywords: O15; C63; C61; O21; J24; 650; project team; proactive planning; competences; robustness; disruptions